1997
DOI: 10.1287/trsc.31.4.324
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Vehicular Traffic Flow using M/G/C/C State Dependent Queueing Models

Abstract: In this paper, M/G/C/C state dependent queueing models are proposed for modeling and analyzing vehicular traffic flows. Congestion aspects of traffic flow are represented by introducing state dependent service rates as a function of number of vehicles on each road link. Analytical models for unidirectional and multisource flows are presented. Finally, queueing models to analytically determine the optimal capacity and performance measures of the road links are incorporated into a series of software programs ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 11 publications
0
87
0
Order By: Relevance
“…For example, in roadway traffic networks it is well known that the vehicle service time deteriorates as a function of the occupancy on the roadway [7]. In human-based service systems, there is a strong correlation between the volume of work demanded from a human and her/his productivity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in roadway traffic networks it is well known that the vehicle service time deteriorates as a function of the occupancy on the roadway [7]. In human-based service systems, there is a strong correlation between the volume of work demanded from a human and her/his productivity.…”
Section: Introductionmentioning
confidence: 99%
“…However one can expect this estimate to grow when δ is picked inadequately large, and at the same time reducing perturbation by several orders can lead to 14 increase in computational complexity and the problem becomes less stable. Hence one should seek a compromise between these two conditions when fixing the order of perturbation.…”
Section: N-class Model: Analysis and Resultsmentioning
confidence: 99%
“…Assume that the file size is distributed generally (with CDF G(.)) with mean 1/α..Using the result for M/G/C/C queues with state dependent service in Smith and Jain [14], we have the probability that there…”
Section: General Distribution For File Sizesmentioning
confidence: 99%
“…Vandaele et al [46] and Heidemann [28], showed that queueing models can also be used to explain uninterrupted traffic flows and thus offers a more practical approach, useful for sensitivity analysis, forecasts, etc. Jain and Smith [32] describe in their paper a state-dependent M/G/C/C queueing model for traffic flows. Part of their logic is used here to extend our queueing models to state-dependent ones.…”
Section: A Queueing Approachmentioning
confidence: 99%